1999
DOI: 10.3171/jns.1999.90.2.0321
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 14C-sucrose delivery to the brain by intravenous, intraventricular, and convection-enhanced intracerebral infusion

Abstract: Chronic CED appears to be a potentially useful method for significantly circumventing the BBB and increasing delivery of water-soluble drugs to the brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(42 citation statements)
references
References 22 publications
2
40
0
Order By: Relevance
“…Firstly, convection-enhanced delivery is a method of local delivery that drives an infusate through the extracellular fluid in neural tissue using a continuous pressure gradient [61]. Experimental studies have shown that convection-enhanced delivery can achieve a local drug concentration 10,000-fold greater than that achieved by intravenous drug administration without causing significant systemic exposure [62, 63]. Secondly, local delivery of chemotherapeutic agents to the brainstem can be achieved via a cannulated screw attached to the skull of the animal [59].…”
Section: Future Directionsmentioning
confidence: 99%
“…Firstly, convection-enhanced delivery is a method of local delivery that drives an infusate through the extracellular fluid in neural tissue using a continuous pressure gradient [61]. Experimental studies have shown that convection-enhanced delivery can achieve a local drug concentration 10,000-fold greater than that achieved by intravenous drug administration without causing significant systemic exposure [62, 63]. Secondly, local delivery of chemotherapeutic agents to the brainstem can be achieved via a cannulated screw attached to the skull of the animal [59].…”
Section: Future Directionsmentioning
confidence: 99%
“…Unlike intraparenchymal injection, CED does not cause structural or functional damage to the infused tissue, and it provides greater control over the distribution of the therapeutic substance. In CED, solutes are distributed homogeneously throughout a distribution volume that is proportional to the infusion volume regardless of the solute's molecular weight (Bobo et al, 1994;Chen et al, 1999;Groothuis et al, 1999;Occhiogrosso et al, 2003). CED is particularly applicable to slowly diffusing substances of high molecular weight because the distribution of such large solutes is effectively restricted to the region of the infusion.…”
mentioning
confidence: 99%
“…49 Investigators compared the concentration of 14 Csucrose in rat brain via intravenous, intrathecal and convectionenhanced delivery and found that convection-enhanced delivery resulted in 10,000-fold increase in tissue concentration of 14 Csucrose versus intravenous delivery. 50 Others have demonstrated that CED of 125 I-boronated epidermal growth factor into rat brains with glioma tumor resulted in 47.4% injected dose/gram (IDg) of the IT being detected within the tumor bed even after 24 hr, whereas intratumoral injection of the IT resulted in only 33% ID/g being detected within the tumor bed 24 hr after injection. 47 To overcome this limitation of DTIL13 in a clinical trial, it is logical that convection-enhanced delivery should be used.…”
Section: Discussionmentioning
confidence: 99%